2018
DOI: 10.5812/iranjradiol.15089
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Ultrasound and Gastrointestinal Series Findings in Detection of Pediatric Intestinal Malrotation

Abstract: Background: Clinical diagnosis of malrotation is difficult to achieve, especially in older children and adults as its nonspecific presentations at this stage are usually neglected leading to delayed diagnosis of these cases. Objectives: In this study, we aimed to evaluate the diagnostic values of ultrasound and upper gastrointestinal (GI) series in patients with suspected intestinal malrotation. Methods: This six-year cross-sectional, prospective study was conducted in Dr. Sheikh Children's Hospital affiliated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…24 In previous work, specificity of sonography was noted as 54.5%, for diagnosis of a rotational anomaly. 9 The result of this study demonstrated some abnormalities besides rotational anomalies, which were noted in association with a mesenteric vessel anomaly. Some of these were the detection of a mass effect and diaphragmatic hernia and have been previously described.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…24 In previous work, specificity of sonography was noted as 54.5%, for diagnosis of a rotational anomaly. 9 The result of this study demonstrated some abnormalities besides rotational anomalies, which were noted in association with a mesenteric vessel anomaly. Some of these were the detection of a mass effect and diaphragmatic hernia and have been previously described.…”
Section: Discussionmentioning
confidence: 52%
“…1218 UGI series have a sensitivity of 93% to 100% and a 15% false positive rate. 1,4,6,9,19 In addition, radiographic studies have problems such as radiation exposure and issues with correct positioning during the radiographic examination. 20 Radiographic barium enemas cannot also be used as a routine test for rotational abnormalities of the bowel and mesenteric vessels because 20% of cases with rotational abnormalities show normal cecum position.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations